Bimbingan Teknis Pembelajaran Anak Berkebutuhan Khusus untuk Guru-Guru Sekolah Menengah Kejuruan - Nara, Hartini; Purnamawati, Siti Nuraini; Sajidah, Hana; Jasmine, Julia (Ilin Institute, 2025)
This technical guidance activity aims to provide understanding to teachers and educational staff to overcome the barriers they face, particularly concerning how to address and meet the learning needs of students with special needs in an inclusive learning environment. The methods used include technical guidance through material delivery and focus group discussion (FGD). The outputs from this activity include positive impacts and an expanded understanding of teachers and educational staff in inclusive vocational high schools in Pekalongan Regency in handling and educating students with special needs, poster, YouTube channel video, news article, as well as the establishment of a partnership between the Special Education Program of the Faculty of Education at Universitas Negeri Jakarta and the Education and Culture Department of Pekalongan Regency.